(3Yed SGYGJ GdeGA GdJi JQei HGdHfGObs
(3ChdgG (B:s
(3EPG GQOJ Pdc aGYeO Edi fMGS aGJNP efg NRGfI ddeGA jchf GQJaGYgG KdGKI CTHGQ ai bWQ THQjf s
(3BNQgG (B:s
(3dfUa GdBf cja fYed QLdkG bGFekG ai beI ReGQg eG ScgG HjOjg aEPG RGdJ GdTeS fUa GdfgGQ ReQ HJdc GdReGQI ReQkG TOjOkG jSeY ef HYjO s
(3HgG CTcGd gfOSjI hQShes
(3ajgG VQhH ef GdMQcGJ efShHI Edi CQTejOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B4 - (3bSe eYGQa YGeI (B- (3U (B176 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdUfGYI hGdCWYeIs